FAKTOR - FAKTOR YANG MEMPENGARUHI KEPUTUSAN WISATAWAN BERKUNJUNG KE AGROWISATA BANYUMILI DI KECAMATAN WONOSALAM KABUPATEN JOMBANG - Fawwas, Bisma Bayu Putra Nias; Yuliati, Nuriah; Setiyadi, Taufik (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This research aims to identify the factors influencing tourists' decisions to visit Banyumili, Wonosalam. The analytical methods used include descriptive statistical analysis and factor analysis. A purposive sampling method was employed, with 100 respondents to assess visitors' perceptions and factors affecting their visits. Exploratory factor analysis was conducted based on the Marketing Mix 7P model. This research indicates two main factors influencing tourists' decisions to visit Banyumili, Wonosalam. These factors are infrastructure, which includes indicators such as tourist attractions, cleanliness, facility completeness, accessibility, location, safety standards, and social media, and the second factor is cost suitability, which includes ticket and food and beverage indicators. Keywords : Factor Analysis; Tourist’s Visiting Decicions; Marketing Mix 7P